BOOK REVIEW: CALIN TEUTIȘAN, "SCENARII ALE CRITICII. PROTAGONIȘTI, METODE, INTERPRETARI", CLUJ-NAPOCA: ȘCOALA ARDELEANA, 2021, 276 P. - LUPAȘCU-DOBOȘ, Emanuel (Studia Universitatis Babeș-Bolyai Philologia, 2022)
Bringing together a series of scientific articles published between 2011 and 2019, Călin Teutișan's book, Scenarios of Criticism. Protagonists, Methods, Interpretations, aims to map the critical spirit of the so-called “Școala de la Cluj” [Cluj School], represented by a series of emblematic figures analyzed in detail. Călin Teutișan’s analytical hypotheses start from empirical data, namely a series of dictionaries and monographic studies published in co-authorship, thus demonstrating “the readiness of these critics to work together” (10). Assuming the concept of la communaute inavouable, belonging to Maurice Blanchot, Călin Teutișan demonstrates that beyond differences between these scholars, there is a certain feeling of “incompleteness” whose counterpart is the feeling of belonging to a community, developing common ideas, obsessions, and methods. The effort to bring together ample critical portraits of Dumitru Popovici, Ioana Em. Petrescu, Liviu Petrescu, Ion Pop, Mircea Muthu, Corin Braga, Alex Goldiș, Emanuel Modoc, Daiana Gârdean, Ovio Olaru, and others is doubled by the welcome contextualization, both historical and theoretical, of each figure or school of thought. This means that a theoretical framework accompanies the deliberately exhaustive and engaged presentations of some Opera Omnia (in the case of well-established critics). One of the merits of this book is bringing forward a productive intellectual dialogue with these critics. Therefore, Călin Teutișan’s critical portraits combine in-depth analyses with synthetic approaches, contextualization, and cultural dialogue. What distinguishes each author analyzed is the style and methodology by which critical works are approached.